Designing a Model for Intergenerational Conflict Management in Iran's Government Organizations - Shirin Eskandari; Mohammad Ataee; Ali Mohtashami (مطالعات منابع انسانی, 2023)
Background & Purpose: The generational diversity in the human force that today's organizations are facing is one of the factors of the spread of conflict in organizations. The purpose of this study is to design a model for intergenerational conflict management in Iran's government organizations.Methodology: Thematic analysis method has been used to conduct this research. The statistical population of this research was formed by academic and organizational experts. In order to collect data, a semi-structured interview was used.Findings: The research resulted in 119 basic themes, 35 organizing themes, as well as 12 comprehensive themes (i.e., civility gap in events of meaningfulness and perceptualization, the gap in the regularization of communication general rules, self-determination framework of job value-driven, environmental-organizational divergences in generational culturalization, authenticity semantic collapse in intergenerational interactions, organizational withdrawal in intergenerational dissimilarity management, intergenerational conflicts in job ideologies, intergenerational uncertainty in job accomplishment quality, task and relational conflict bilinear orientations, selective criteria in choosing conflict management style, functionalist conflict management strategies, and interpretive conflict management strategies).Conclusion: Based on the findings, it can be claimed that in order to better understand intergenerational conflicts, it is essential to find the root of the disputed areas in the structure of perceptions of generational differences, and in formulating the types of strategies, it is necessary to consider both areas of discord and conflict in the reactional way.